ANALISIS DINAMIKA BEBAN HARIAN DAN PELUANG LOAD SHIFTING PADA GEDUNG SEKOLAH - Rahmah, Aulia (Micronic: Journal of Multidisciplinary Electrical and Electronics Engineering, 2025)
Energy consumption management in schools is an important aspect of efficiency and operational cost control efforts. This study analyses daily load dynamics and identifies opportunities for load shifting at SMK Negeri 4 Gowa based on data on device usage duration and installed power in each functional room. The data is converted into hourly energy consumption to form a daily load curve. The analysis results show that there is a peak load during core activity hours, triggered by the simultaneous operation of high-power equipment such as air conditioners, lights, and computers. Consumption patterns also indicate potential inefficiencies due to uncontrolled device usage that does not take into account actual room conditions. This study offers an energy management strategy in the form of load shifting, which is carried out by redistributing the use of certain devices to off-peak hours without disrupting learning activities. In addition, changes in user behaviour and device operation settings can significantly reduce monthly energy consumption. Thus, the data-based energy management approach applied in this study can provide real energy and cost savings and support the creation of a more efficient and sustainable school environment.